Case Report: Immunophenotypically diverse immature patterns, including variable TdT expression, in aggressive B-cell lymphomas and leukemia with MYC rearrangement - Kato, Daishi; Fujino, Takahiro; Isa, Reiko; Okamoto, Haruya; Tsukamoto, Taku; Mizutani, Shinsuke; Shimura, Yuji; Kobayashi, Tsutomu; Uchiyama, Hitoji; Taniwaki, Masafumi; Miyagawa-Hayashino, Aya; Kuroda, Junya (Frontiers in Oncology, 2025)
This study is a retrospective analysis of our case series and literature review of aggressive B-cell lymphomas with MYC rearrangements that show immunophenotypic immaturity, including expression of terminal deoxynucleotidyl transferase (TdT), weak or negative CD20, and the absence of surface membrane immunoglobulin (smIg) and light chains. Although classified as diffuse large B-cell lymphoma (DLBCL) or high-grade B-cell lymphoma (HGBCL), these cases sometimes resemble B-lymphoblastic leukemia/lymphoma (B-ALL/LBL) immunophenotypically, creating diagnostic ambiguity. We report four cases: three diagnosed as HGBCL-MYC/BCL2 with TdT expression, and one as B-ALL with MYC rearrangement. Case 1 developed from follicular lymphoma with TdT-positive blastoid transformation. Case 2 showed widespread disease, complex cytogenetics, weak TdT positivity, and absence of light chain. Case 3 displayed scattered TdT expression and surface light chain restriction. Case 4, initially diagnosed as a mature B-cell neoplasm, was ultimately reclassified as B-ALL with MYC rearrangement and focal TdT expression. In all cases, CD20 expression was weak or negative. These overlapping immunophenotypes between mature B-cell neoplasms and lymphoblastic leukemia were also documented in previous reports of 89 patients with various MYC-rearranged mature B-cell lymphoma subtypes. Through review, we identified the patient population with tumor cells showing less than 10% positive TdT expression, weak or negative CD20, and absence of smIg and light chain expression. Conversely, B-ALL with MYC rearrangement also exhibits aberrant immunophenotypes, such as negative to weak TdT expression and variable CD20, smIg, or light chain expression. Notably, this phenotypic immaturity appears closely linked to the presence of MYC rearrangement. In contrast, recent studies have shown that TdT-positive DLBCL/HGBCL-MYC/BCL2 and B-ALL with MYC rearrangement have distinct molecular features. In conclusion, an analysis of 93 cases, including our four cases, suggests that MYC rearrangement contributes to immature immunophenotypic profiles in both lymphoma and leukemia, emphasizing the importance of a refined classification that integrates morphology, immunophenotype, and genetics.